Effect of seasonality and physicochemical parameters on bacterial communities in two hot spring microbial mats from Araró, Mexico - Cristina M. Prieto-Barajas; Ruth Alfaro-Cuevas; Eduardo Valencia-Cantero; Gustavo Santoyo (Revista Mexicana de Biodiversidad)
In this study, we explored the diversity of culturable bacterial communities residing in hot springs from Araró, México, and analysed the effect of seasonality and related changes in physicochemical parameters of spring water. Two hot springs with unique features, Tina and Bonita, were analysed. Seventy-nine unique 16S rRNA gene phylotypes were detected, belonging to the bacterial phyla Firmicutes, Proteobacteria, and Actinobacteria. A group of dominant phylotypes of the genus Bacillus was recovered in 3 out of 4 of the sampling seasons. Another group of phylotypes was recovered in 2 samplings, while the remaining groups were detected in only 1 season. Ecological indexes for species richness and evenness showed moderate to low diversity in both hot springs, and a Sørensen analysis revealed that the 2 communities shared 64% of their bacterial phylotypes. Physicochemical parameters measured every season showed slight variations, except for temperature and arsenic content. Fluctuations in bacterial composition in the Tina hot spring were correlated mainly with salt content, while diversity in the Bonita hot spring was significantly correlated with temperature, pH, and arsenic content.